PENERIMAAN METODE PEMBALAJARAN BERBASIS E-LEARNING DI DAYAH JEUMALA AMAL LUENG PUTU, PIDIE JAYA - Bustami Yusuf; Hendri Ahmadian; Masrura Mailany; Basrul Abdul Majid; Yusran Asnawi (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2017)
The growth of Information Technology (IT) has changed the order of conventional learning process toward the learning model without geographical boundaries, which is known as E-learning. This study aims to explore the readiness of Dayah Jeumala Amal Lueng Putu to implement the E-learning method by using ELR Aydin & Tasci data analysis model. The results of this study has shown that Dayah Jeumala Amal is ready to implement learning system based on E-learning except on Human Resources factor (2.99) and Innovation factor (3.11). The highest score is on Technology factor (4.02), followed by self-development factor (3.57). This study contributes to educational institutions to improve the quality of human resources and innovation in the implementation of learning methods based on E-learning.